Application of Double Exponential Smoothing Method and Dashboard Visualization to Analyze Sales Transaction Data at PT Natural Nusantara Partnership (Case Study: Stockis BG.3005 Muara Enim) - Tasriq Tasriq; Suzi Oktavia Kunang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study discusses the application of the BI roadmap method and the double exponential smoothing method. The BI roadmap method is used in building a business intelligence dashboard to evaluate product sales of PT. Natural Nusantara on Stockist BG.3005 Muara Enim and double exponential smoothing are used to forecast sales at Stockist BG.3005 Muara Enim for the next period. The application of the two methods showed that sales in 2020-2021 decreased, the best-selling product categories were cosmetic and body care, household, health, and agrocomplex products, and also got the 5 most interested products, namely Nasa Toothpaste, Moreskin: Clean & Glow Cream, Grece AntiPerspirant, Quwless : Liquid Hygiene For Man and Shanas : Shampoo 3 in 1. Forecasting on the five products for January 2022, namely, Nasa Toothpaste = 33 items, Moreskin : Clean & Glow Cream = 2 item , Grece AntiPerspirant = 3 items, Quwless : Liquid Hygiene For Man = 2 items, and Shanas : Shampoo 3 in 1 = 4 items.